2010
DOI: 10.1089/fpd.2010.0576
|View full text |Cite
|
Sign up to set email alerts
|

Determining Relationships Between the Seasonal Occurrence ofEscherichia coliO157:H7 in Live Cattle, Ground Beef, and Humans

Abstract: The prevalence and concentration of many foodborne pathogens exhibit seasonal patterns at different stages of the farm-to-table continuum. Escherichia coli O157:H7 is one such pathogen. While numerous studies have described the seasonal trend of E. coli O157:H7 in live cattle, ground beef, and human cases, it is difficult to relate the results from these different studies and determine the interrelationships that drive the seasonal pattern of beef-related human illnesses. This study uses a common modeling appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…The NPST test chooses a 6-month long significant seasonal increase running from May through October (p = 0.013). This seasonal increase is very similar, in terms of both onset and duration, to the seasonal increases in illness observed in FoodNet for Salmonella and E. coli O157:H7 (Williams et al, 2010(Williams et al, , 2014.…”
Section: Seasonal Patternssupporting
confidence: 73%
See 2 more Smart Citations
“…The NPST test chooses a 6-month long significant seasonal increase running from May through October (p = 0.013). This seasonal increase is very similar, in terms of both onset and duration, to the seasonal increases in illness observed in FoodNet for Salmonella and E. coli O157:H7 (Williams et al, 2010(Williams et al, , 2014.…”
Section: Seasonal Patternssupporting
confidence: 73%
“…For example, ground beef has been implicated in the majority of the E. coli O157:H7 related outbreaks in the United States and this product-pathogen pair has the highest estimated attribution fraction (Painter et al, 2013). A time series analysis for E. coli O157:H7, using methods similar to those employed here, demonstrated a nearly perfect correspondence in the seasonal patterns between live cattle, ground beef and human illnesses (Williams et al, 2010). A similarly strong seasonal pattern between chicken and campylobacteriosis cases has been observed in Iceland (Lowman et al, 2009;Tustin et al, 2011), where a substantial reduction in campylobacteriosis cases was observed after an aggressive control program was implemented to reduce Campylobacter contamination of chicken.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…3,4 E. coli O157:H7/NM is a pathogen with worldwide distribution, [5][6][7][8][9][10][11] with infections more commonly reported in northern latitudes 1,12 and in the summer. [13][14][15] E. coli O157:H7/NM may be carried by a wide range of animals, with cattle and other domestic ruminants recognized as important reservoirs. 16,17 Human infection can occur via consumption of contaminated food and beverages, recreational waters, and contact with humans or animals shedding the bacterium.…”
mentioning
confidence: 99%
“…Given the evidence linking human infection to the bovine reservoir, it is likely that the reduction of STEC O157 shedding in cattle during summertime might result in reduced carcass contamination rates at the abattoir and, ultimately, reduced human disease burden (29,30).…”
mentioning
confidence: 99%